Assessment of the applicability of multi-satellite precipitation products on the Loess Plateau over the past four decades - Rui Liu; Liu Yang; Zhengguo Shi; Mengdao Xing (International Journal of Applied Earth Observations and Geoinformation)
The study of drought and precipitation evolution due to global warming has garnered significant attention from the scientific community in recent years. The Loess Plateau (LP), a typical dryland agricultural area, has its agricultural development influenced by precipitation. However, given its location in the hinterland of the Eurasian continent, the complex terrain, and the severe lack of rain gauges, the region faces challenges in accurate precipitation measurement. Multi-satellite precipitation products (MPPs), with their wide coverage and high resolution, can potentially address this deficiency, making it crucial to assess their applicability on the LP. This study evaluates the results of the inversion of LP precipitation changes by MPPs, the factors influencing the precipitation changes, and the dynamical mechanisms affecting LP precipitation evolution. The findings indicate that the CPC is the most suitable product for inverting daily precipitation on the LP, with the highest correlation coefficient of 0.774 between CPC and observations, and the highest Probability of Detection of 0.667. This is attributed to the stable data sources and excellent algorithms used by CPC. Furthermore, the LP has exhibited a significant upward trend in precipitation since 2000, with the thermal term playing a significant role in the humidification of the LP. The analysis suggests that global warming increases atmospheric moisture content, and enhanced westerly jet and near-surface easterly anomalies transport warm, humid air from the North Atlantic and the eastern China Sea into the LP. Clarifying the precipitation trends and dynamics in the LP can provide valuable policy support for agricultural development.